Correlation between doctor's belief on the patient's self-determination and medical outcomes in obtaining informed consent - Yoshihara, Keisuke; Takase, Kozo (Journal of medical and dental sciences, 2013)
We employed a questionnaire survey to assess attitudes toward informed consent (IC) among hospital doctors. Based on the result of the correlation analysis, the following two hypotheses were identified. The first hypothesis is that "the doctor's belief that the patient's self-determination is possible promotes cure of illness by obtaining IC." The second hypothesis is that "the doctor's belief that the patient's self-determination is possible has a positive influence on patient's quality of life by obtaining IC." We clarified the rationale for explaining these two hypotheses by applying cross tabulation analysis, discriminant analysis and principal component analysis (PCA). The doctors were divided into two groups in terms of their position on the patient's self-determination. One group of doctors believed the possibility of patient's self-determination, and the other did not. Through our statistical analyses, the characteristics that discriminate these two groups were identified. It was revealed that the former group placed a great importance on the hospitality value, while the latter placed an importance on the service value. Agreement or rejection of the concept of IC has been demonstrated as a key distinguishing factor between the two groups. The results of PCA showed that the doctor's belief on the patient's self-determination in obtaining IC had a significant effect on medical outcomes, and the two above-mentioned hypotheses were revealed.